Estudo fitoquímico e atividade biológica de Qualea paraensis Ducke (Vochysiaceae) - Aroucha, Keyla Mayara Mian (2015)
This paper describes the phytochemical study and biological evaluation of the ethanol extract of Qualea paraensis Ducke belonging to Vochysiaceae família. The botanical material was collected in the municipality of Rorainópolis, located 294 km from the capital Boa Vista. The ethanol extract of peel was partitioned with solvents and fractions yielded in hexane, chloroform, ethyl acetate and methanol. The chloroform fractions were analyzed by classical chromatographic methods and determined whether antioxidante activity, antimicrobial, analysis of cytotoxic activity and potential inhibition of acetylcholinesterase. The toxicity evaluation was conducted using the toxicity test facing the microcrustaceans Artemia salina with LD50. The antioxidant activity was determined by the kidnapping radical 2, 2-diphenyl-1picrilhidrazil (DPPH) in methanol means determining the antioxidant and EC50 percentage. The antimicrobial activity was tested using the technique of microdilution broth and were read on a spectrophotometer, acetylcholinesterase activity was also determined using ELISA reader spectrophotometer. The structural identification means are infrared spectra, proton magnetic resonance spectra 1H and 13C 135 type DEPT, COSY, HSQC and HMBC. The crude ethanol extract showed low antifungal activity to fungi Aspergillus flavus and Fusarium proliferatum. It was noticed a moderate action of antimicrobial action for E. coli bacteria and S. sanguinis reaching 64.59% of the percentage of inhibition. He showed no inhibitory activity of the enzyme acetylcholinesterase and low toxicity against Artemia salina.